Guinea : Technical Assistance Report-Report on Technical Assistance Mission on External Sector Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Technical Assistance report on Guinea addressed issues like: improvement of the surveys on migrant remittances and informal trade; perform detailed technical work to improve external sector statistics (ESS); and participation in the coordinated direct investment survey and the quarterly external debt statistics database. The mission observed that the recommendations from the previous technical assistance mission had been satisfactorily implemented. The report also describes that the timeliness of ESS, based on international standards, should be improved, mainly for the international investment position and the quarterly balance of payments statistics. In order to contribute to progress in the areas discussed in the report, the mission made a one-year detailed action plan, with priority given to the recommendations of importance in improving ESS. The recommendation on reporting reinvested earnings of direct investment enterprises, net increases in insurance company liabilities, and income on reserve assets has partially been implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet